Phenoxypropylamines: Synthesis and Antiulcer Evaluation - Dong-Mei Zhao; Jia-Mei Wang; Qian-Yun Zhang; Bao-Yan Zhang; Hui Zhang (Molecules, 2009)
We have synthesized a number of phenoxypropylamines from N-{3-[3-(1-piperidinylmethyl)phenoxy]propyl}chloroacetamide (3). All the products have been characterized by elemental analysis, 1H-NMR and MS. The biological activity effects of the title compounds were examined. From the biological activity results, we found that two of themshowed significant gastric acid antisecretory activity.